Highly symmetrical crystallization in six rectilinear and well-defined axes found in bovine cervical mucus obtained at oestrus: a finding. artículo corto (2014)
Bovine cervical mucus (BCM) is important for selection and transport of spermatozoa. When air-dried, BCM obtained at oestrus exhibits arborescent crystallizations, among other arrangements. Considering the relevant endocrine and reproductive information indirectly obtained from BCM crystallization, a morphological investigation was carried out to study its crystalline patterns. BCM samples were collected from healthy Holstein Friesan heifers at oestrus, their crystalline patterns photographed and its morphology analyzed. The majority of the crystallizations obtained showed the typical arboriform patterns reported for BCM. However, a highly symmetrical arrangement was found, characterized by a star-like morphology with six straight, highly defined axes that protrude from the same central point, forming 60º angles. In terms of our knowledge, this short report is the first to show this crystallization geometry in BCM, which, additionally, is remarkably similar to P6B mucus reported for periovulatory human cervical mucus. Even though the role of mucus presenting this type of crystallization is as yet unknown for bovines, its possible functions are also briefly discussed here.